An Ultrahigh‐Density Microneedle Array for Skin Vaccination: Inducing Epidermal Cell Death by Increasing Microneedle Density Enhances Total IgG and IgG1 Immune Responses. Issue 8 (9th May 2022) - Coffey, Jacob W.; van der Burg, Nicole M. D.; Rananakomol, Thippayawan; Ng, Hwee-Ing; Fernando, Germain J. P.; Kendall, Mark A. F.
Abstract : Many types of microneedle (MN) arrays have been tested for delivery of vaccines to the skin. However, the effect of MN geometry/array design on antibody production is still unclear. Reports suggest that systemic immune responses may be affected by how MN arrays "mechanically" deliver vaccines, which can induce cell damage and act as an adjuvant. This includes parameters such as MN length/insertion depth, delivery energy/velocity, MN shape, and density. However, these effects have not been systematically investigated. Herein, the effect of MN density on antibody responses to influenza vaccination is assessed, keeping all other variables constant. MN arrays are manufactured within the "high‐density range" from 5 k microneedles cm −2 (n cm −2 ) to the "ultrahigh" 30 k n cm −2 . Prior to this study, the highest MN density used for vaccination is 20 k n cm −2 . Thus, MN array vaccination is evaluated over an unprecedented range. Cell viability is assessed in the skin after application and antibody responses at days 21/63. It is demonstrated that increasing MN density from 5 to 30 k n cm −2 increases both epidermal cell death and anti‐influenza IgG1, without an increase in anti‐influenza IgG2a. This suggests that MN density has a direct adjuvant effect on immune responses through Th2‐mediated signalling—a response critical for human vaccination. Abstract : "Physical adjuvantation"—a process caused by the mechanical disruption of tissue, inducing cell death and the release of immune stimulating danger signals during vaccination (similar to that of traditional skin scarification techniques)—is proposed herein to have been achieved by increasing microneedle array density during transdermal vaccination and was shown to increase IgG1 but not IgG2a antibody responses in mice.